Looking Back at Law's Century - Garth, Bryant; Kagan, Robert A.; Sarat, Austin (Cornell University Press, 2018)
This book describes a century of tremendous legal change, of inspiring legal developments, and profound failures. The twentieth century took the United States from the Progressive Era's optimism about law and social engineering to current concerns about a hyperlegalistic society, from philosophical idealism to the implementation of democracy, the rule of law, and the idea of human rights throughout the world. At the same time, law maintained its status as the key language of governance in the United States, the most "legal" of all countries, which has succeeded in making its version of the state a point of reference around the globe.